Review of the scientific journal “Publicaciones en Ciencias y Tecnología” (issn: 2477-9660) of the Universidad Centroccidental Lisandro Alvarado (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of the scientific journal "PUBLICACIONES EN CIENCIAS Y TECNOLOGÍA" (ISSN: 2477-9660) of the Universidad Centroccidental Lisandro Alvarado, Venezuela. This means of scientific dissemination was founded in 2007, attached to the Dean of Sciences and Technology of said university, every six months, has the purpose of contributing to the dissemination of scientific works in the areas of mathematics, physics, chemistry, computing engineering and technological sciences, from national and international researchers. It is indexed in DOAJ, Revencyt, Latindex catalog, Redib, Dialnet and Periódica.
Keywords: science and technology; physics; mathematics; engineering; scientific journal; UCLA; Venezuela